Peran Lembaga Pendidikan Islam dalam Memberdayakan Sumber Daya Manusia yang Berdaya Saing Global - Pithriani Pithriani; Musyarapah Musyarapah (Departement of Mathematics Education, 2024)
Islamic educational institutions have an important role in empowering human resources (HR) that are able to compete globally. This research examines the role of Islamic educational institutions in developing competitive human resources through an adaptive curriculum that combines modern science with Islamic values, innovative learning methods, and strong character building programs. This approach produces individuals who are professionally competent, moral, and able to contribute in the global market. Using qualitative methods and literature review, this study reveals that the academic and moral integration carried out by Islamic educational institutions is able to prepare a generation with high integrity and competence to face global challenges.